PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 5E UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII7 SMPN 14 PEKANBARU - Trisna Gusvitasari; Sehatta Saragih; Zuhri Zuhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is a class action research that aims to improve the learning process and to increase the outcomes of mathematics learning of the students by applying learning cycle 5E. The subjects of this research are the students of class VII7 SMPN 14 Pekanbaru at the second semester of academic years 2017/2018 as many as 35 students with heterogeneous ability. This research consist two cycles. Each of them has four stages: planning, implementation, observation, and reflection. Learning device used in this research consists of Syllabus, Lesson plan, and Student work sheet. The data collecting instruments consist observation sheet (learning process) and mathematics achievement test. The data were analized by narrative descriptive and statistical descriptive analysis. The data were obtained from the observation sheets of teacher and students activities that showed the learning process has improved after the model being implemented. Data obtained from students mathematics achievement test showed that the frequency of students who reach the category of good enough and very good is increasing from the basic score to quiz I and from quiz I to quiz II on competency in knowledge and skill. Other than that, the percentage of students who achieved KKM competency knowledge from basic score to quiz I increased by 20% and from quiz I to quiz II increased by 22,86% and competency skill from basic score to quiz I increased by 20% and from quiz I to quiz II increased by 11,43%. In conclusion, the implementation of learningcycle 5E model can improve the learning process and increase the outcomes of mathematics learning of the students of grade VII7 SMPN 14 Pekanbaru at the second semester of academic years 2017/2018 on rectangular and triangular materials.Key Words: Learning Outcomes of Mathematics, Learning Cycle 5E